Bantuan Operasional Sekolah (BOS): Antara Aturan VS Implementasi di Sekolah Dasar Negeri 1 Padaherang Kecamatan Padaherang Kabupaten Pangandaran - Diyar Sugiarti (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
There are still problems with the use of school operational funds, both in terms of coverage and use. This study aims to identify several problems, namely: How is the implementation, limitations and efforts to provide BOS financing for educational equity in SD Negeri 1 Padaherang in 2022. In this study the technique used was qualitative data analysis techniques using observation, interview and study techniques data. Based on the findings and discussion results regarding the use of School Operational Assistance funds, SDN 1 Padaherang in the implementation of the allocation of BOS funds has achieved success and is running on target in a directed manner. starting with the planning, implementation, monitoring and evaluation stages of implementation. BOS funds are used to pay for natural benefits, such as finding library reference works, paying for non-teaching activities, tests and exams. Implementation was constrained by delays in BOS funds at each payment stage and a lack of human resources such as the BOS Treasurer to use ARKAS (School Activity Plan and Budget Application). This causes difficulty in generating usage reports. Efforts to overcome obstacles in managing BOS funds are to first seek recovery funds, meanwhile schools provide technical guidance and ARKAS reporting training through the Cluster KKG group to fill gaps in ARKAS understanding that must be overcome.